2013
DOI: 10.2139/ssrn.2210925
|View full text |Cite
|
Sign up to set email alerts
|

Are South East Europe Stock Markets Integrated with Regional and Global Stock Markets?

Abstract: This paper analyses whether stock markets of South East Europe (SEE) have become more integrated with regional and global stock markets during 2000s. Using a variety of co-integration methodologies we show that SEE stock markets have no long-run relationship with their mature counterparts. This means that SEE markets might be immunized to external shocks. We also model time varying correlations among these markets by using Multivariate Generalised Autoregressive Conditional Heteroschedastic (MGARCH) models as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…They indicated that the MOEX index lacked an appropriate transmission channel or mechanism from informed investors to the other markets. Guidi and Ugur (2013) indicated that the correlation structures between the U.K., the U.S. and the southern and eastern European equity markets had changed over time around the subprime crisis between 2007 and 2009. Thalassinos et al (2015) found that there existed different channels of influence in the developed western European countries, the U.S. and Japan, i.e., the mature capital markets, and in the southern and eastern European emerging countries (Greece, Romania, Hungary, Poland, and Slovenia) during the subprime crisis.…”
Section: Empirical Research Of Contagion Effectmentioning
confidence: 99%
“…They indicated that the MOEX index lacked an appropriate transmission channel or mechanism from informed investors to the other markets. Guidi and Ugur (2013) indicated that the correlation structures between the U.K., the U.S. and the southern and eastern European equity markets had changed over time around the subprime crisis between 2007 and 2009. Thalassinos et al (2015) found that there existed different channels of influence in the developed western European countries, the U.S. and Japan, i.e., the mature capital markets, and in the southern and eastern European emerging countries (Greece, Romania, Hungary, Poland, and Slovenia) during the subprime crisis.…”
Section: Empirical Research Of Contagion Effectmentioning
confidence: 99%
“…The data is consist of Stock index closing prices weekly from January 2, 1991 to July 6, 2017. We use weekly prices to minimize effects of cross-country differences in weekend market closures 3 . Because China and US stock market trading day is slightly different, this paper deletes some transaction data that two markets do not overlap.…”
Section: Data Selection and Processingmentioning
confidence: 99%